Partial‐body cryotherapy (−135°C) and cold‐water immersion (10°C) after muscle damage in females. (27th November 2019) - Hohenauer, Erich; Costello, Joseph T.; Deliens, Tom; Clarys, Peter; Stoop, Rahel; Clijsen, Ron
Abstract : This randomized controlled trial examined the effects of cold‐water immersion (CWI), partial‐body cryotherapy (PBC), or a passive control (CON) on physiological and recovery variables following exercise‐induced muscle damage (EIMD, 5 × 20 drop jumps) in females. Twenty‐eight females were allocated to PBC (30 seconds at −60°C, 2 minutes at −135°C), CWI (10 minutes at 10°C), or CON (10 minutes resting). Muscle oxygen saturation (SmO2 ), cutaneous vascular conductance (CVC), mean arterial pressure (MAP), and local skin temperature were assessed at baseline and through 60 minutes (10‐minute intervals), while delayed onset of muscle soreness (DOMS), muscle swelling, maximum voluntary isometric contraction (MVIC), and vertical jump performance (VJP) were assessed up to 72 hours (24‐hour intervals) following treatments. SmO2 was lower in PBC (Δ‐2.77 ± 13.08%) and CWI (Δ‐5.91 ± 11.80%) compared with CON (Δ18.96 ± 1.46%) throughout the 60‐minute follow‐up period ( P < .001). CVC was lower from PBC (92.7 ± 25.0%, 90.5 ± 23.4%) and CWI (90.3 ± 23.5%, 88.1 ± 22.9%) compared with CON (119.0 ± 5.1 and 116.1 ± 6.6%, respectively) between 20 and 30 minutes ( P < .05). Mean skin temperature was lower from CWI vs PBC (between 10 and 40 minutes, P < .05). Mean skin temperature was higher in CON compared with CWI up to 60 minutes and compared with PBC up to 30 minutes ( P < .05). DOMS was lower following both PBC and CWI compared with CON through 72‐hour ( P < .05), with no difference between groups. No main group differences for swelling, MVIC, and VJP were observed. In conclusion, CWI elicited generally greater physiological effects compared with PBC while both interventions were more effective than CON in reducing DOMS in females, but had no effect on functional measures or swelling.